Calculations of gaseous and particulate emissions from German agriculture 1990-2013: Report on methods and data (RMD) Submission 2015; Berechnung von gas- und partikelförmigen Emissionen aus der deutschen Landwirtschaft 1990-2013: Report zu Methoden und Daten (RMD) Berichterstattung 2015 - Claus Rösemann; Hans-Dieter Haenel; Ulrich Dämmgen; Annette Freibauer; Sebastian Wulf; Brigitte Eurich-Menden; Helmut Döhler; Carsten Schreiner; Beate Bauer; Bernhard Osterburg (Johann Heinrich von Thünen-Institut, 2015)
The report at hand (including a comprehensive annex of data) serves as additional document to the National Inventory Report (NIR) on the German green house gas emissions and the Informative Inventory Report (IIR) on the German emissions of air pollutants (especially ammonia). The report documents the calculation methods used in the German agricultural inventory model GAS-EM as well as input data, emission results and uncertainties of the emission reporting submission 2015 for the years 1990 - 2013. In this context the sector Agriculture comprises the emissions from animal husbandry, the use of agricultural soils and anaerobic digestion of energy plants. As required by the guidelines, emissions from activities preceding agriculture, from the use of energy and from land use change are reported elsewhere in the national inventories. The calculation methods are based in principle on international guidelines for emission reporting and have been continuingly improved during the past years. In particular, these improvements concern the calculation of energy requirements, feeding and the N balance of the most important animal categories. In addition, technical measures such as air scrubbing (mitigation of ammonia emissions) and digestion of animal manures (mitigation of emissions of methane and loughing gas) have been taken into account. Total emissions of methane (CH4) and laughing gas (N2O) from German agriculture (including the anaerobic digestion of energy plants) decreased from about 77.9 Tg CO2-eq in 1990 to about 64.2 Tg CO2-eq in 2013 (- 17.5 %). [...] – – Der vorliegende Berichtsband einschließlich des umfangreichen Datenanhangs dient als Begleitdokument zum National Inventory Report (NIR) über die deutschen Treibhausgas-Emissionen und zum Informative Inventory Report (IIR), über die deutschen Schadstoffemissionen (insbesondere Ammoniak). Er dokumentiert die im deutschen landwirtschaftlichem Inventarmodell GASEM integrierten Berechnungsverfahren sowie die Eingangsdaten, Emissionsergebnisse und Unsicherheiten der Berichterstattung 2015 für die Jahre 1990 bis 2013. Der Bereich Landwirtschaft umfasst dabei die Emissionen aus der Tierhaltung und der Nutzung landwirtschaftlicher Böden sowie aus der Vergärung von Energiepflanzen. Emissionen aus dem Vorleistungsbereich, aus der Nutzung von Energie sowie Landnutzungsänderungen werden den Regelwerken entsprechend an anderer Stelle in den nationalen Inventaren berichtet. Die Berechnungsverfahren beruhen in erster Linie auf internationalen Regelwerken zur Emissionsberichterstattung und wurden in den vergangenen Jahren beständig weiterentwickelt. Letzteres betrifft im Wesentlichen die Berechnung des Energiebedarfs, der Fütterung und der tierischen N-Bilanz bei den wichtigen Tierkategorien. Zusätzlich wurden technische Maßnahmen wie Abluftreinigung (Minderung von Ammoniakemissionen) und die Vergärung von Wirtschaftsdünger (Minderung von Methan- und Lachgasemissionen) berücksichtigt. Die Gesamtemissionen von Methan (CH4) und Lachgas (N2O) aus der deutschen Landwirtschaft (einschließlich der Vergärung von Energiepflanzen) sanken von rund 77,9 Tg CO2-eq im Jahr 1990 auf rund 64,2 Tg CO2-eq im Jahr 2013 (-17,5 %). [...]
urn:nbn:de:gbv:253-201504-dn055107-8
Keywords: 630; emission inventory; agriculture; animal husbandry; agricultural soils; anaerobic digestion; energy plants; renewable primary products; greenhouse gases; air pollutants; methane; loughing gas; ammonia; particulate matter; Emissionsinventar; Landwirtschaft; Tierhaltung; landwirtschaftliche Boden; anaerobe Vergarung; Energiepflanzen; nachwachsende Rohstoffe; Treibhausgase; Luftschadstoffe; Methan; Lachgas; Ammoniak; luftgetragene Partikel